Optic nerve head and retinal nerve fiber layer analysis in emmetropic Malay children - Ahmad, Ameilia (2016)
Background Optic nerve head (ONH) parameters and retinal nerve fiber layer thickness (RNFLT) of normal children have been described in previous published reports. None of these measurements was described among Malay children population using Cirrus spectral domain optical coherence tomography (SD-OCT). The aim was to report normative values for ONH parameters and RNFLT in emmetropic Malay children. The possible correlations between these parameters were also evaluated. Objectives To determine the mean of ONH parameters and mean RNFL in emmetropic Malay children; and to determine correlation between the ONH parameters and RNFL thickness Methods Ninety-five Malay children with no ocular abnormality aged between 7 to 17 years were recruited into this cross sectional study. It was conducted in Hospital Universiti Sains Malaysia, Malaysia from January 2014 to December 2015. All children underwent a complete ocular examination including refraction and axial length measurement. ONH parameters and RNFLT measurement were performed using Cirrus SD-OCT machine. One eye of each subject was randomly selected for analysis. The correlations in between the parameters and influence of age, gender,axial length and spherical equivalent (SE) on measurements were statistically evaluated. Results Ninety-five children were included in the study with 65 females (68.4%) and 30 males (31.6%). Mean age was 10.6 (2.82) years, mean IOP was 14.8 (2.81) mmHg, mean SE refraction was -0.12 (0.28) diopters and mean axial length was 23.03 (0.76) mm. Mean (SD) disc area, rim area and cup volume were 2.32 (0.40) mm2, 1.53 (0.33) mm2 and 0.204 (0.16) mm3, respectively. The average cup to disc ratio (SD) and vertical CDR were 0.55 (0.13) and 0.50 (0.14). Mean (SD) RNFLT for all patients was 102.08 (11.08) μm. The average, superior and inferior RNFLT showed a significant positive correlation with the optic disc area. A significant correlation was also observed between the rim area and average, superior, inferior and nasal RNFLT. The inferior RNFLT was negatively correlated with average CDR. There was also significant effect of gender on disc area. There were no significant effects of age, axial length and SE on the measurements. Conclusion This study provides normative data of ONH parameters and RNFLT in emmetropic Malay children. Emmetropic Malay male had a significantly larger optic disc area. Increase in RNFLT is associated with significant increase in disc and rim areas.